Reproductive biology of the Gorgona guitarfish, Pseudobatos prahli, in the central-eastern Pacific Ocean - Prieto-Veloz, Mary Cruz; Calle-Morán, Marcos Douglas; Tovar-Ávila, Javier (Revista de Biología Marina y Oceanografía, 2022)
Pseudobatos prahli is considered a low-medium fishing importance species in Ecuador, caught as target species and bycatch in both artisanal and industrial fisheries. Despite its importance, some basic aspects of its biology remain unknown, turning its study a priority. The aim of the present research was to describe for the first time the reproductive biology of P. prahli based on the analysis of individuals landed in the port of Santa Rosa, Province of Santa Elena, Ecuador. A total of 96 females and 165 males were sampled from January 2013 to January 2014. Females presented larger sizes (51-86 cm total length, TL) than males (51-78 cm TL), but no significant differences were found between the mean sizes of both sexes. The sexual proportion of landed individuals (0.6F:1M) suggested that free-living individuals segregate by sex, however, sex proportion of embryos was similar to the proportion 1F:1M. The number of mature individuals (64%) in the landings was larger than the immature ones (36%). Mean size at maturity (L50) of females (65.9 cm TL) was also slightly larger than that for males (61.8 cm TL). Size at birth was estimated at 22.5 cm TL. Ovarian fecundity ranged from 1 to10 and uterine fecundity from 1 to 6, and a positive but low linear relationship was found between both fecundity estimates and maternal size. Based on the comparison of some reproductive parameters, such as mean size at maturity, gestation period and fecundity, it can be concluded that P. prahli is one of the species with lowest biological productivity among the species of the same genus.